A four phase development model for integrated care services in the Netherlands - Huijsman Robbert; Ahaus Kees TB; Minkman Mirella MN (BMC, 2009)
Abstract Background Multidisciplinary and interorganizational arrangements for the delivery of coherent integrated care are being developed in a large number of countries. Although there are many integrated care programs worldwide, the process of developing these programs and interorganizational collaboration is described in the literature only to a limited extent. The purpose of this study is to explore how local integrated care services are developed in the Netherlands, and to conceptualize and operationalize a development model of integrated care. Methods The research is based on an expert panel study followed by a two-part questionnaire, designed to identify the development process of integrated care. Essential elements of integrated care, which were developed in a previous Delphi and Concept Mapping Study, were analyzed in relation to development process of integrated care. Results Integrated care development can be characterized by four developmental phases: the initiative and design phase; the experimental and execution phase; the expansion and monitoring phase; and the consolidation and transformation phase. Different elements of integrated care have been identified in the various developmental phases. Conclusion The findings provide a descriptive model of the development process that integrated care services can undergo in the Netherlands. The findings have important implications for integrated care services, which can use the model as an instrument to reflect on their current practices. The model can be used to help to identify improvement areas in practice. The model provides a framework for developing evaluation designs for integrated care arrangements. Further research is recommended to test the developed model in practice and to add international experiences.